1999
DOI: 10.1080/152165499306874
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Complexity of a Rice Transgene Locus Susceptible to Methylation-Based Silencing

Abstract: Molecular analyses of a rice (Oryza sativa L.) transgene locus introduced using biolistic techniques revealed the presence of multiple copies of rearranged fragments, as well as an intact copy of the supplied constructs. Both the gene of interest (35S-Btt cryIIIA) and the selectable marker used (Ubi1-bar) were methylated and silenced. Additionally, vector sequences were present in great abundance and were also highly methylated, indicating that the entire transgene insert was marked for methylation. The rearra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Ho et al (2000) reported that this promoter contributes disproportionally to genomic instability; however, this conclusion is based on misinterpretation of the literature. The 35S promoter contains a recombination hotspot, associated with an imperfect 19-bp inverted repeat (Kohli et al, 1999), with the consequence that many transformants show rearrangements in the region (Kumpatla and Hall, 1999). Ho et al (2000) overlooked the fact that the reported rearrangements occurred in the plasmids used for transformation, not in the plants.…”
Section: Can Transgenes Alter Genome Stability? Transgene Instabilitymentioning
confidence: 99%
“…Ho et al (2000) reported that this promoter contributes disproportionally to genomic instability; however, this conclusion is based on misinterpretation of the literature. The 35S promoter contains a recombination hotspot, associated with an imperfect 19-bp inverted repeat (Kohli et al, 1999), with the consequence that many transformants show rearrangements in the region (Kumpatla and Hall, 1999). Ho et al (2000) overlooked the fact that the reported rearrangements occurred in the plasmids used for transformation, not in the plants.…”
Section: Can Transgenes Alter Genome Stability? Transgene Instabilitymentioning
confidence: 99%
“…Hot spots for rearrangement in 35S promoter regions have been reported in transgenic maize (Register et al 1994) and transgenic rice (Kohli et al 1999;Kumpatla and Hall 1999). Aberrant/non-Mendelian transgene segregation has been frequently reported in transgenic plants.…”
Section: Resultsmentioning
confidence: 97%
“…Chen et al (1998) reported that the majority of R1 transgenic wheat progeny showed little or no expression of the chitinase gene when under control of the 35S promoter, while the PAT gene under control of the maize ubiquitin promoter was functional. It has been proposed that genomic surveillance processes may recognize the 35S promoter as an intrusive viral sequence, thus initiating an inactivation mechanism (Kumpatla and Hall 1999). At both the tillering and heading stages of development, the RUBQ2 promoter conferred a threefold increase in stable GUS expression over the RUBQ1 promoter.…”
Section: Resultsmentioning
confidence: 99%
“…Line JKA52 was identified as a single locus line that expressed both cryIIIa and bar genes. The transgene insert in JKA52, estimated to be about 150 kb in size, contains multiple rearranged copies of the transgenes (Kumpatla and Hall, 1999), but segregates as a single locus (Kumpatla and Hall, 1998b). Among expressing and silenced progenies, line JKA52-10 was characterized as having transcriptionally silenced mUbi1 and 35S promoters by nuclear run-on and RNase protection experiments.…”
Section: Establishment Of a Homozygous 35s And Mubi1 Transcriptionallmentioning
confidence: 99%
“…Given these changes in understanding of TGS, we decided to use a well-defined transgenic rice line (Kumpatla et al, 1997;Kumpatla and Hall, 1999) in which the mUbi1-bar component was transcriptionally silenced to reinvestigate HDTGS. On the basis that DNA sequence homology leads to HDTGS, we anticipated that supertransformation with a construct driven by an identical promoter (e.g.…”
Section: Introductionmentioning
confidence: 99%